Long-term outcomes of endoscopic resection and tailored adjuvant radiotherapy for sinonasal intestinal-type adenocarcinoma: a historical single-center cohort study in 200 patients - Parys, Quentin-Alexandre; De Witte, Matthias; Hauben, Esther; Clement, Paul M.; Hermans, Robert; Decramer, Thomas; van Loon, Johannes; Nuyts, Sandra; Jorissen, Mark; Vander Poorten, Vincent; Van Gerven, Laura (Frontiers in Oncology, 2025)
BackgroundSinonasal intestinal-type adenocarcinoma (ITAC) is a rare disease entity. In contrast to most previous studies, this cohort study consists of a substantial number of uniformly treated patients undergoing endoscopic surgery and adjuvant radiotherapy and provides updated insights into survival outcomes and tumor and treatment-related prognostic factors.Material and methodsWe retrospectively analyzed the medical records of 200 patients primarily treated for ITAC between 1992 and 2022 in our tertiary referral center. Descriptive statistics were applied using Kaplan-Meier method. Cox models were used for univariable and multivariable data analysis.ResultsThe 5-year overall survival (OS), disease-specific survival (DSS), and local recurrence-free survival (LRFS) rates were 71.4%, 85.1%, and 55.2% respectively. At 10 years, the numbers decreased to 48.2%, 76.2%, and 32.2% respectively. Significant differences were found in OS and DSS between T-groups. Poorly differentiated tumors had decreased DSS compared to well-differentiated tumors (HR: 3.38 [95% CI: 1.20–9.51], p=.0209). Signet-cell differentiation was associated with the poorest survival among poorly differentiated tumors although not reaching significance. In 34.0% of patients, there was local recurrence, with half of the cases detected within the first two years of follow-up but over 10% of recurrence occurring after 10 years. Positive surgical margins (HR: 2.95 [95% CI: 1.29–6.74], p=.0106), local recurrence (HR: 12.28 [95% CI: 5.59–26.99], p<.0001), and distant metastasis (HR: 41.17 [95% CI: 21.58–78.55], p<.0001) negatively affected DSS. Distant metastasis occurred more frequently in poorly differentiated tumors (25.6%) compared to moderately differentiated (9.5%) and well-differentiated tumors (2.5%) (p=.002).ConclusionsThis extensive study focusing on sinonasal ITAC primarily managed through endoscopic resection and radiotherapy, demonstrates that T-classification and tumor differentiation are independent prognostic factors influencing survival. Furthermore, local recurrence, distant metastasis, and positive surgical margins negatively affect OS and DSS.